Diagnostic Accuracy of Ultrasonography and Radiography in Initial Evaluation of Chest Trauma Patients - Vafaei, Ali; Hatamabadi, Hamid Reza; Heidary, Kamran; Alimohammadi, Hosein; Tarbiat, Mohammad (Archives of Academic Emergency Medicine, 2018)
Introduction: Application of chest radiography for all multiple trauma patients is associated with a significant increase in total costs, exposure to radiation, and overcrowding of the emergency department. Ultrasound has been introduced as an alternative diagnostic tool in this regard. The aim of the present study is to compare the diagnostic accuracy of chest ultrasonography and radiography in detection of traumatic intrathoracic injuries. Methods: In the present prospective cross-sectional study, patients with traumatic intrathoracic injuries, who were referred to the emergency department from December 2013 to December 2014, were assessed. The patients underwent bedside ultrasound, radiographic and computed tomography (CT) scan examinations based on ATLS recommendations. Screening performance characteristics of ultrasonography and radiography were compared using SPSS 21.0. Chest CT scan was considered as gold standard. Results: 152 chest trauma patients with a mean age of 31.4 ± 13.8 years (range: 4 ‒ 67), were enrolled (77.6% male). Chest CT scan showed pulmonary contusion in 48 (31.6%) patients, hemothorax in 29 (19.1%), and pneumothorax in 55 (36.2%) cases. Area under the ROC curve of ultrasonography in detection of pneumothorax, hemothorax, and pulmonary contusion were 0.91 (95% CI: 0.86‒0.96), 0.86 (95% CI: 0.78‒0.94), and 0.80 (95% CI: 0.736‒0.88), respectively. Area under the ROC curve of radiography was 0.80 (95% CI: 0.736‒0.87) for detection of pneumothorax, 0.77 (95% CI: 0.68‒0.86) for hemothorax, and 0.58 (95% CI: 0.5‒0.67) for pulmonary contusion. Comparison of areas under the ROC curve declared the significant superiority of ultrasonography in detection of pneumothorax (p = 0.02) and pulmonary contusion (p < 0.001). However, the diagnostic value of the two tests was equal in detection of hemothorax (p = 0.08). Conclusion: The results of the present study showed that ultrasonography is preferable to radiography in the initial evaluation of patients with traumatic injuries to the thoracic cavity.